Effects of Pig Slurry Coupled with Straw Mulching on Soil Nitrogen Dynamics and Maize Growth - Yali Yang; Dengchao Lei; Yulan Zhang; Zhe Zhao; Hongtu Xie; Fangbo Deng; Xuelian Bao; Xudong Zhang; Hongbo He (Agronomy)
The balanced application of organic and chemical fertilizers is essential for maintaining soil fertility and crop productivity. To optimize nitrogen (N) balance and maize yield through integrated pig slurry and straw mulching management, a split-plot field experiment was conducted in Northeast China. The study included two straw treatments (straw mulching, S; no straw, NS) and three substitution levels of pig slurry for chemical fertilizer (0%, 20%, and 40%; denoted as M0, M20, and M40). Parameters evaluated included N balance, maize biomass, soil available N, and the mineral N to TN ratio (mineral-N/TN), measured across 0–100 cm at key maize growth stages. Results showed that pig slurry substitution significantly increased soil DON, mineral N, and mineral-N/TN in the topsoil (0–20 cm) at the maize seeding stage and decreased mineral-N/TN at the maize milk (10–40 cm) and maturity (80–100 cm) stages. Meanwhile, straw mulching reduced NH4+-N accumulation in the 0–10 cm of topsoil at the seeding stage, decreased NO3−-N in the 0–40 cm soil layer from the jointing to maturity stages, and lowered the mineral-N/TN ratio in the topsoil, thereby mitigating the risk of N leaching. Notably, the combination of pig slurry substitution and straw mulching slightly increased DON and NO3−-N in the topsoil while significantly reducing the mineral-N/TN in the deep soil layer at the seeding and milk stages. Pig slurry substitution significantly improved maize yield, N uptake, and N use efficiency (NUE). The highest maize yield (14,628 kg ha−1) was observed in the S-M20 treatment, representing a 19% increase compared to NS-M0. N balance analysis indicated that pig slurry substitution alone increased maize yield and N uptake but depleted soil N, whereas straw mulching maintained N surplus. The findings highlight that combining pig slurry with straw mulching optimizes soil N availability and improves sustainable N management and crop productivity in agroecosystems.